Dampak Melewatkan Sarapan pada Remaja - Kasenda, Telvie Laura; Arief, Yuni Sufyanti; Indarwati, Retno; Yunara, Yulia (Journal of Telenursing (JOTING), 2024)
This study aims to analyze scientific articles that examine the impact of skipping breakfast on adolescents. The method used is a systematic review and The Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) is used as a guideline. The results of this study indicate that skipping breakfast has a negative impact on cognitive performance and academic achievement in adolescents. In addition, it can also increase the risk of more serious health conditions such as cardiometabolic disorders and other non-communicable diseases along with adolescent development. Conclusion, breakfast is one of the important factors in adolescent health and development, so skipping breakfast will have a negative impact on adolescents. Intervention strategies are needed from the individual, family, school, and government levels in improving adolescent nutrition. Keywords: Academic Achievement, Adolescent, Breakfast Skipping, Cognitive Performance